Integral Sacristán. - Juncosa, Xavier; Juncosa, Xavier; Benach, Joan; López Arnal, Salvador 1954- (El Viejo Topo, 2008)
Sobre la vida y obra de Manuel Sacristán Luzón, el más importante filósofo español del siglo XX